Никита Шаповал о сущности нации как социального феномена - Юренко, А. (Социология: теория, методы, маркетинг, 2001)
The theory of nation created by Mykyta Shapoval — the founder of sociology in Ukraine — is discussed in the article. Sociological aspect of nation as a complicated social community is distinguished. The main trends of discussion devoted to socio logical interpretations of the national identity phenomenon which took place among Ukrainian social scientists on emigration in the beginning of the 20-th century are presented.